COUNSELING: HOW TO PREPARE PIG FEED WITH CONVENTIONAL METHODS - Sri Hartini; Andoyo Supriyantono; Lambertus Eugenus Nuhuyanan; Bambang Tjahjono Hariadi; Trisiwi Wahyu Widayati; Sangle Yohanes Randa; Stepanus Pakage; Marlyn Nelce Lekitoo; Alousius P.E Widodo; Hanike Monim; Lukas Y. Sonbait; Rizki Arizona; Dwi Djoko Rahardjo (Ann Publisher, 2024)
Livestock commodities that are business opportunities for the Papua region are pig farming businesses. According to community culture, pigs are livestock commodities used in traditional ritual ceremonies. The time and place of the community service implementation will be held on December 2, 2023. The extension team will conduct counseling at the Sairo Village Hall. The extension team started the activity at around 11:00 WIT after meeting with the head of Sairo village. The participants who attended were 22 people. The community service method is conducted through counseling through lectures and discussions. Leaf Leat assisted with this lecture. The result was that 22 people in Sairo Village attended the community service activity, supported and attended by the Sairo Village Chief; the event went smoothly, with enthusiastic participants asking questions during the discussion session. Community service activities conclude that counseling has been given, and it is hoped that it can be practiced by the people of Sairo village using local feed in the surrounding environment.